Comparison between two different operation strategies for a heat-driven residential natural gas-fired CHP system: Heat dumping vs. load partialization. (15th December 2016) - Mongibello, Luigi; Bianco, Nicola; Caliano, Martina; Graditi, Giorgio
Highlights: The schedule optimization of a residential cogeneration system is performed. Two different operation strategies are compared. The effects of the size variation of the thermal energy storage system are reported. Results in terms of economic and primary energy savings, and pollutants emission are shown. Abstract: In this work, the results coming from the schedule optimization of a residential natural gas-fired CHP system operating according to a novel heat-driven operation strategy, based on the possibility to dump part of the thermal energy produced by the CHP system, are compared with the ones relative to the case in which the CHP system operates following a heat-driven strategy allowing load partialization. The effects of the variation of the size of the thermal energy storage system on the optimization results are also investigated. The simulation of the two different operation strategies has been realized using a numerical code written in Matlab environment, and a heuristic algorithm has been used for the economic optimization of the operation relative to both the implemented strategies. From the economic point of view, results show that the difference between the best CHP system configuration in the case with heat dumping and the one relative to the case with load partialization is minimal, with the latter presenting a slightly higher economic performance. Moreover, conditions in which heat dumping could yield higher economic performances than load partialization are also presented in this work. As concerns pollutants emissions, results show that the impact of load partialization on a local scale is much higher, with CO emissions that can be up to three times the ones relative to conventional systems for the separate generation of electricity and heat.